Effects of Different Nitrogen Doses on the Agricultural and Chemical Properties of Fennel (Foeniculum vulgareMill.) - TUNCTURK, MURAT (Asian Journal of Chemistry, 2010)
Fertilization is one of the main factors affecting yield and quality in medicinal and aromatic plants like in other traditional crops. In this concept, the effects of four different nitrogen doses (0, 20, 40 and 60 kg ha-1) on the yield and quality of fennel were investigated. Field trials were conducted by completely randomized design with three replications at experimental area located in Gevas-Cicekli district of Van, Turkey, in the years of 2001 and 2002. In this study, plant height, the number of branches, the number of umbrella, seed yield and essential oil yield of fennel were investigated. As a result, the highest plant height (59.3 cm) and essential oil yield (13.9 L ha-1) values were determined in 60 kg ha-1 nitrogen application. The highest the number of branches (6.1 branches plant-1), the number of umbrella (10.98 umbrellas plant-1) and seed yield 665.0 kg ha-1) values were obtained from 40 kg ha-1 nitrogen application.